Effect of postharvest ethylene treatment on sugar content, glycosidase activity and its gene expression in mango fruit - Chidley, Hemangi G.; Deshpande, Ashish B.; Oak, Pranjali S.; Pujari, Keshav H.; Giri, Ashok P.; Gupta, Vidya S. (Journal of the Science of Food and Agriculture, 2017)
BACKGROUND: Ripening-associated softening is one of the important attributes that largely determines the shelf-life of mango (Mangifera indica Linn.) fruits. To reveal the effect of pre-climacteric ethylene treatment on ripening-related softening of Alphonso mango, ethylene treatment was given to mature, raw Alphonso fruits. Changes in the pool of reducing and non-reducing sugars, enzymatic activity of three glycosidases: ss-D-galactosidase, alpha-D-mannosidase and ss-D-glucosidase and their relative transcript abundance were analysed for control and ethylene treated fruits during ripening. RESULTS: Early activity of all the three glycosidases and accelerated accumulation of reducing and non-reducing sugars on ethylene treatment was evident. ss-D-Galactosidase showed the highest activity among three glycosidases in control fruits and marked increase in activity upon ethylene treatment. This was confirmed by the histochemical assay of its activity in control and ethylene treated ripe fruits. Relative transcript abundance revealed high transcript levels of ss-D-galactosidase in control fruits. Ethylene-treated fruits showed early and remarkable increase in the ss-D-galactosidase transcriptswhile alpha-D-mannosidase transcript variants displayed early accumulation. CONCLUSION: Thefindings suggest reduction in the shelf-life of Alphonso mango upon pre-climacteric ethylene treatment, a significant role of ss-D-galactosidase and alpha-D-mannosidase in the ripening related softening of Alphonso fruits and transcriptional regulation of their expression by ethylene. (C) 2016 Society of Chemical Industry